2014
DOI: 10.1007/s12041-014-0387-7
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression analysis of an anthocyanidin synthase gene homologue from Brassica carinata

Abstract: 2014 Cloning and expression analysis of an anthocyanidin synthase gene homologue from Brassica carinata. J. Genet. 93, 513-516]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…EBGs ( chalcone synthase , CHS ; chalcone isomerase , CHI ; flavanone 3-hydroxylase , F3H ; flavonoid 3’-hydroxylase , F3’H ) are the common flavonoid pathway genes which are involved in the biosynthesis of all downstream flavonoids. LBGs ( dihydroflavonol 4-reductase , DFR ; anthocyanidin synthase/leucoanthocyanin dioxygenase , ANS / LDOX ; uridine diphosphate-glucose: flavonoid 3-O-glucosyltransferase , UFGT ) are genes regulating the biosynthesis of anthocyanins ( Petroni and Tonelli, 2011 ; Yan et al, 2014 ; Liu et al, 2018 ). The EBGs are regulated by a class of R2R3–MYB transcription factors, while the regulation of LBGs requires a ternary complex of MYB–bHLH–WD40 (MBWs), which binds the promoters of target genes and then activate their transcription, leading to a higher accumulation of the anthocyanin level ( Lepiniec et al, 2006 ; Xu et al, 2014 ; Kim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…EBGs ( chalcone synthase , CHS ; chalcone isomerase , CHI ; flavanone 3-hydroxylase , F3H ; flavonoid 3’-hydroxylase , F3’H ) are the common flavonoid pathway genes which are involved in the biosynthesis of all downstream flavonoids. LBGs ( dihydroflavonol 4-reductase , DFR ; anthocyanidin synthase/leucoanthocyanin dioxygenase , ANS / LDOX ; uridine diphosphate-glucose: flavonoid 3-O-glucosyltransferase , UFGT ) are genes regulating the biosynthesis of anthocyanins ( Petroni and Tonelli, 2011 ; Yan et al, 2014 ; Liu et al, 2018 ). The EBGs are regulated by a class of R2R3–MYB transcription factors, while the regulation of LBGs requires a ternary complex of MYB–bHLH–WD40 (MBWs), which binds the promoters of target genes and then activate their transcription, leading to a higher accumulation of the anthocyanin level ( Lepiniec et al, 2006 ; Xu et al, 2014 ; Kim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…ANS is encoded by a mini-gene family in many plants. ANS gene have been cloned and functionally analyzed in Theobroma cacao (Liu et al, 2013), Brassica carinata (Yan et al, 2014), Brassica juncea (Yan et al, 2011), Fructus mori (Qi et al, 2014), Punica granatum L. (Ben-Simhon et al, 2015), Malus spectabilis (Zhang et al, 2015), and Pyrus communis L. ; however, few reports on regulation of anthocyanin accumulation by ANS gene in peach fruit skin are available. In the present study, an ANS gene (PpANS) was isolated from peach fruit skin by using RT-PCR technique to determine the function of PpANS in peach fruit.…”
Section: Cloning Of Full-length Cdna Of Ppansmentioning
confidence: 99%
“…The anthocyanin content of yellow raspberry decreased significantly [ 23 ]. The BjANS gene of Brassica juncea was expressed in both black seed coat and embryo, while in yellow seed coat, the deletion of BjANS gene expression prevented the biosynthesis of proanthocyanidins, so the seeds were yellow due to the transparency of the seed coat [ 24 ]. Eun-Young Kim et al [ 25 ] identified two new allelic variants of ANS genes, which could cause the deletion of onion anthocyanin synthesis.…”
Section: Introductionmentioning
confidence: 99%